Pengaruh Kualitas Pelayanan, Lokasi Dan Fasilitas Terhadap Kepuasan Dan Loyalitas Pengujung Warkop Daun Kopi Di Kota Makassar - salma (Insan Cita Bongaya Research Journal, 2021)
This study aims to examine the effect of: quality of service, location, facilities on visitor satisfaction and visitor loyalty at coffee shops in Makassar City. The sample of this research is 44 visitors who often come. The analytical tool used to reveal information uses WarpPLS. The results of the study of service quality, location, facilities have a positive and significant effect on visitor satisfaction. Furthermore, visitor satisfaction has a positive and significant effect on visitor loyalty. All relationships between variables show significant so that the results of the study are getting closer to the SERVQUAL theory.